2015
DOI: 10.1177/0192623315608509
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Phospholipidosis Is Associated with Altered Hepatobiliary Function as Assessed by Gadoxetate Dynamic Contrast–enhanced Magnetic Resonance Imaging

Abstract: To determine if amiodarone induces hepatic phospholipidosis (PLD) sufficient to detect changes in hepatobiliary transporter function as assessed by gadoxetate dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI), rats were orally dosed with vehicle (1% methyl cellulose) or amiodarone (300 mg/kg/day) for 7 consecutive days. Gadoxetate DCE-MRI occurred at baseline, day 7, and following a 2-week washout of amiodarone. At day 7, the gadoxetate washout rate was significantly decreased compared to the vehi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Neither the established biomarkers of liver injury, aspartate aminotransferase, alanine aminotransferase and alkaline phosphatase, nor the novel biomarker miRNA-122, showed a difference between rifampicin and vehicle treated groups two hours after dosing with rifampicin. This confirms the results of Lenhard et al where changes in transporter function were observed without an increase in liver injury enzymes [ 19 ]. In contrast, both total and direct bilirubin were elevated.…”
Section: Discussionsupporting
confidence: 92%
“…Neither the established biomarkers of liver injury, aspartate aminotransferase, alanine aminotransferase and alkaline phosphatase, nor the novel biomarker miRNA-122, showed a difference between rifampicin and vehicle treated groups two hours after dosing with rifampicin. This confirms the results of Lenhard et al where changes in transporter function were observed without an increase in liver injury enzymes [ 19 ]. In contrast, both total and direct bilirubin were elevated.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, as MRI, US, and CT imaging can be used to monitor treatment effects during studies, recovery of these effects can also be monitored to determine the permanence of treatment or return animals to colonies, for example, thereby promoting the 3Rs. For example, Lenhard et al (2016) applied dynamic contrast-enhanced MRI to detect changes in hepatobiliary transporter function as a result of amiodarone-induced hepatic phospholipidosis before, during, and 2 weeks after cessation of amiodarone treatment. The calculated rates of contrast agent wash-out, which is dependent on efflux transporter function, decreased with treatment and fully recovered after cessation of treatment.…”
Section: Use For Safetymentioning
confidence: 99%